Hydrotropism: how roots search for water - Dietrich, Daniela (Oxford University Press, 2018)
Fresh water is an increasingly scarce resource for agriculture. Plant roots mediate water uptake from the soil and have developed a number of adaptive traits such as hydrotropism to aid water foraging. Hydrotropism modifies root growth to respond to a water potential gradient in soil and grow towards areas with a higher moisture content. Abscisic acid (ABA) and a small number of genes, including those encoding ABA signal transducers, MIZ2/GNOM, and the hydrotropism-specific MIZ1, are known to be necessary for the response in Arabidopsis thaliana, whereas the role of auxin in hydrotropism appears to vary depending on the plant species. This review will describe recent progress characterizing the hormonal regulation of hydrotropism. Recent advances in identifying the sites of hydrotropic perception and response, together with its interaction with gravitropism, will also be discussed. Finally, I will describe putative mechanisms for perception of the water potential gradient and a potential role for hydrotropism in acclimatizing plants to drought conditions.